A new termite species (Isoptera: Termitidae: Termitinae: Amitermes) and first record of a Subterranean Termite from the Coastal Desert of South America - Scheffrahn, Rudolf H.; Huchet, Jean-Bernard (Zootaxa, 2010)
At about one hundred species (Scheffrahn & Su 1987), Amitermes, is the second largest genus after Microcerotermes in the subfamily Termitinae. This cosmopolitan genus is found in a wide variety of habitats from rainforests e.g., Amitermes excellens (Silvestri) from Guyana (Emerson 1925) and Amitermes dentatus (Haviland) from Sumatra (Gathorne-Hardy et al. 2001) to deserts, e.g. Amitermes emersoni Light from Coachella, California (Light 1930) and Amitermes desertorum Desneux from Egypt (Sands 1992). Only eight species of Amitermes are known from the Neotropics and only five occur across mainland South America. Soldiers of Amitermes are characterized by a bulbous head capsule and sickle-shaped mandibles, each with a single tooth of various shapes on their inner margins. Soldiers of all species have a large cephalic gland opening to a circular fontanelle on the frons. When confronted by an agonist, the soldier emits a terpenoid secretion which oozes onto setae around and below the fontanelle (Scheffrahn et al. 1983). Herein, is described a new Amitermes from Peru and the first record of a subterranean termite along the Pacific coastal desert of South America.